Extremismos políticos e direitas Bolsonaro, Trump e a crise das "democracias" - Barbosa, Jefferson Rodrigues (Editora Oficina Universitária, 2022)
Different in their historical particularities and political and ideological singularities, these objects under analysis are understood as a concrete historical manifestation of the crisis situation on the right, in the Brazilian context with Bolsonaro and internationally with different national specificities. From the criterion of valuing the historical particularities and singularities of social phenomena, the expressions of the rights make up differences in their axioms. However, in addition to historical and national particularities and singularities, these manifestations of right-wing political extremism have a common element, which are forms of political expression which legitimize bourgeois autocracy as universality, reflecting the logic of class conflict.